Masyarakat Adat Balai Kiyu : Menghadapi Ancaman Eksistensi Di Tanah Sendiri - Dimas Asto Aji An’Amta; Ismar Hamid; Muhammad Luthfi Fahrizan (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
The Balai Kiyu Indigenous People are the Dayak indigenous people who have long occupied the Meratus mountain region in South Kalimantan. These indigenous people have problems that will threaten their existence. The problem is not internal, but external parties overshadowing communal well-being. This study aims to analyze the threats that will be faced by the Balai Kiyu Indigenous Peoples to their existence and is expected to represent the threats that will be faced by indigenous peoples along the Meratus mountains. Based on the research results obtained, the threat to the existence of the Indigenous Peoples Kiyu Centers among them is, first, the boundaries of indigenous territories so far that has not been authorized by the regional or central government, making them very vulnerable communities. Secondly, the highly educated generation slowly began to abandon local wisdom that had been running for decades from its negative effects. Third, the Omnibus Law Bill on the Labor Copyright Act will clarify that indigenous peoples in the future will only be named, because of the loss of communal ownership rights so far.